Modern Requirements for Future Elementary Technology Education Teachers (Journal of Pedagogical Inventions and Practices, 2023)
Scientific and methodological work on developing the competence of prospective teachers to receive information involves integrating information-related subjects with public science, creating integrated programs and textbooks.